Transistor Probes Local Potassium Conductances in the Adhesion Region of Cultured Rat Hippocampal Neurons - Vassanelli, Stefano (J Neurosci, 1999)
Adhesion interactions of neurons in a tissue may affect the ion conductance of the plasma membrane, inducing selective localization and modulation of channels. We studied the adhesion region of cultured neurons from rat hippocampus as a defined model where such effects could be observed electrophysiologically, taking advantage of extracellular recording by a transistor integrated in the substrate. We observed the K(+) current through the region of soma adhesion under voltage-clamp and compared it with the current through the whole cell. We found that the specific A-type conductance was depleted, even completely, in the region of adhesion, whereas the specific K-type conductance was enhanced up to a factor of 12. The electrophysiological approach opens a new way to investigate targeting of ion channels in the cell membrane as a function of adhesion processes.